The Effectiveness of Make a Match Cooperative Learning on Problem Solving Ability and Mathematics Learning Outcomes of Elementary School Students - Marten Mare; Marwati Abdul Malik; Suroyo Suroyo (Edumaspul: Jurnal Pendidikan, 2023)
This research was conducted to analyze the effectiveness of the make a match cooperative learning model effective on problem solving skills and mathematics learning outcomes of elementary school students. The data collected is in the form of student ability numbers which are measured by test instruments given before and after treatment. The quantitative data were analyzed using the t test to analyze the comparison of the pretest posttest data and the gain n test to see the increase in students' abilities. The t value of problem solving ability is 19.406 > 1.7108 and the gain value is 0.34007. For the t test the results of learning mathematics are 16.153> 1.7108. In addition, the value of n gain is 0.56652, this shows that cooperative learning of the make a match type is effective for problem solving abilities and students' mathematics learning outcomes.